CHANGES IN STRESS LEVELS IN PATIENTS FOR AGE HYPERTENSION AFTER GETTING MUSIC THERAPY - Verronica R. Daromes; Maria Terok; Femmy Lumi (Jurnal Ilmiah Perawat Manado (Juiperdo), 2019)
Background: Stress is the response of the body and mind to everything that disturbs a person's balance. Stress can also be experienced by anyone without knowing the age limit and has a long-term effect, it also results in to increase in disease conditions one of which is hypertension in every stage of human life, especially in the elderly (Elderly). One of non-pharmacological method that can reduce blood pressure is by providing music therapy. Aims: This study to determine music therapy for changes in stress levels in elderly hypertensive patients. The design of this study is analytic operational using the cross-sectional approach. Methods: was analytic correlation using a cross-sectional approach. The population in this study amounted to 214 people. A sample of 21 respondents was obtained using a purposive sampling technique, and data were collected using the DASS (Depression Anxiety Stress Scale) questionnaire and a blood pressure measurement tool for sphygmomanometers. Result: Chi-Square analysis with an alternative test is the Exact Test using SPSS. The results of the study stress levels in elderly hypertensive patients are in the mild category that is 81%. This shows that there is a significant relationship between stress levels and hypertension in elderly hypertension patients with significance level α = 0.05 or 95% value ρ = 0.012 <α = 0.05. Conclusion: The conclusion is the relationship of music therapy to changes in stress levels in elderly hypertensive patients in the working area of ​​the Tateli Health Center in Mandolang District. Suggestions for future researchers This study can be used as a reference to increase knowledge in carrying out nursing care in hypertensive patients, especially it is recommended that you use an audiometry device in order to know the level of hearing.